Bright photoluminescence from ordered arrays of SiGe nanowires grown on Si(111) - Lockwood, D. J.; Rowell, N. L.; Benkouider, A.; Ronda, A.; Favre, L.; Berbezier, I. (Beilstein Journal of Nanotechnology, 2014)
We report on the optical properties of SiGe nanowires (NWs) grown by molecular beam epitaxy (MBE) in ordered arrays on SiO2/Si(111) substrates. The production method employs Au catalysts with self-limited sizes deposited in SiO2-free sites opened-up in the substrate by focused ion beam patterning for the preferential nucleation and growth of these well-organized NWs. The NWs thus produced have a diameter of 200 nm, a length of 200 nm, and a Ge concentration x = 0.15. Their photoluminescence (PL) spectra were measured at low temperatures (from 6 to 25 K) with excitation at 405 and 458 nm. There are four major features in the energy range of interest (980–1120 meV) at energies of 1040.7, 1082.8, 1092.5, and 1098.5 meV, which are assigned to the NW-transverse optic (TO) Si–Si mode, NW-transverse acoustic (TA), Si–substrate–TO and NW-no-phonon (NP) lines, respectively. From these results the NW TA and TO phonon energies are found to be 15.7 and 57.8 meV, respectively, which agree very well with the values expected for bulk Si1−xGex with x = 0.15, while the measured NW NP energy of 1099 meV would indicate a bulk-like Ge concentration of x = 0.14. Both of these concentrations values, as determined from PL, are in agreement with the target value. The NWs are too large in diameter for a quantum confinement induced energy shift in the band gap. Nevertheless, NW PL is readily observed, indicating that efficient carrier recombination is occurring within the NWs.
Keywords: bandgap; germanium; nanowires; near field; silicon; photoluminescence